EVALUASI PENGELOLAAN ASET LABORATORIUM KOMPUTER MENGGUNAKAN STANDAR ISO/IEC 27001 - Fahmi Husaeni; Nina Sulistiyowati; Adhi Rizal (LPPM STMIK Pringsewu, 2018)
Computer laboratory UNSIKA is a vital facility belonging to the computer science faculty of the university singaperbangsa karawang because it is used to conduct teaching and learning activities practicum. Evaluated the management of computer lab assets UNSIKA using ISO 27001 standard in clause A.8 Assets Management to overcome the problem in asset management. The assets in question (Hardware, Software, Human, Information, Infrastructure and Outsourcing Services) use quantitative research methods and ISO evaluation stage model starting from scoping, planning, implementation, analysis, reporting and closing. The goal is to improve the quality of the management of computer lab assets UNSIKA. This study uses the stages of ISO evaluation with data collection methods from questionnaires with a scattered likert scale for the lab and user respondents. The result of this research is got the value of maturity of asset management of computer laboratory UNSIKA in clause A.8 Assets Management equal to 1,22 still in level 1 (Initial) there is no standard process or procedure in some asset management activities in manual and still applied approach specific to each activity undertaken in asset management.